2020
DOI: 10.4314/tjpr.v19i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Propofol affects the biological behavior of ovarian cancer SKOV3 cells via ERK1/2-MMP-2/9 signaling pathway

Abstract: Purpose: To investigate the effect of propofol on the biological behavior of ovarian cancer SKOV3 cells, and the mechanism of action involved. Methods: SKOV3 cells cultured in vitro were randomly divided into control group, fat emulsion group, low-dose propofol group (LDPG, 25 μmol/L), medium-dose propofol group (MDPG) (50 μmol/L) and high-dose propofol group (HDPG) (100 μmol/L). Apoptosis was determined by flow cytometry, while Transwell assay was used to measure the migration and invasion abilities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition to the advantages of various anaesthesia, the drug can also exert some nonanaesthetic effects. Relevant studies have shown that propofol has the ability to inhibit tumour proliferation and has a positive effect on the prognosis of surgically treated tumour patients [14]. In vitro, experimental studies have proved that propofol inhibits the invasion and migration of liver cancer cells in liver cancer cells [15].…”
Section: Influence Of Different Concentrations Of Propofol On Fasn Mr...mentioning
confidence: 99%
“…In addition to the advantages of various anaesthesia, the drug can also exert some nonanaesthetic effects. Relevant studies have shown that propofol has the ability to inhibit tumour proliferation and has a positive effect on the prognosis of surgically treated tumour patients [14]. In vitro, experimental studies have proved that propofol inhibits the invasion and migration of liver cancer cells in liver cancer cells [15].…”
Section: Influence Of Different Concentrations Of Propofol On Fasn Mr...mentioning
confidence: 99%
“…Propofol increased the migration of breast cancer cells when compared with a long‐chain triglyceride control [111]. Propofol also induced migration via upregulation of Snail family transcriptional repressor 1, an EMT‐inducing transcription factor [112], and via regulation of extracellular‐signal‐regulated kinase/matrix metalloproteinase signaling [113]. Isoflurane also enhanced metastasis and invasion in ovarian cancer [19] and cervical carcinoma [114].…”
Section: Influence Of Propofol and Isoflurane On Varied Mechanisms Of...mentioning
confidence: 99%